Vous êtes sur la page 1sur 12

Solutions for 2007 A Level H2 Maths Paper 1

1 L.H.S
2 x 2 − x − 19
= 2 −1
x + 3x + 2

=
(
2 x 2 − x − 19 − x 2 + 3 x + 2 )
2
x + 3x + 2
2
x − 4 x − 21
= 2 = R.H.S (shown)
x + 3x + 2

2 x 2 − x − 19
Then >1
x 2 + 3x + 2
2 x 2 − x − 19
−1 > 0
x 2 + 3x + 2
x 2 − 4 x − 21
>0
x 2 + 3x + 2
( x − 7 )( x + 3) > 0
( x + 2 )( x + 1)
( x − 7 )( x + 3)( x + 2 )( x + 1) > 0
∴ x < −3 or − 2 < x < −1 or x > 7

1
2 f ( x) = , x≠3
x −3
g( x) = x 2 , x ∈ 
(i) D f =  \ {3} Dg = 
R f =  \ {0} R g = [0, ∞)

For fg to exist, R g ⊆ Df .
Since R g = [0, ∞)   \ {3} = D f , fg does not exist.

For gf to exists, R f ⊆ D g
Since R f =  \{0} ⊆  = D g , gf exists.
1
gf ( x) = g[f ( x)] = , x≠3
( x − 3)2
D gf =  \ {3}

1
1
(ii) Let y =
x −3
1
x−3 =
y
1
x = 3+
y
1
∴ f −1 ( x) = 3 + , x∈ , x ≠ 0
x
D f -1 = R f =  \{0}

3(a) z + 2 − 3i = 3
z − (−2 + 3i ) = 3
Since −2 + 3i = 4 + 9 = 13 , the circle passes through the origin.

Im

z − (−2 + 3i) = 13

(-2, 3)

13

O Re

3(b) Let w = a + ib
Then w* = a − ib
Now ww* + 2w = 3 + 4i
(a + ib)(a − ib) + 2(a + ib) = 3 + 4i
a 2 − i 2b 2 + 2a + 2ib = 3 + 4i
(a 2
)
+ b 2 + 2a + 2ib = 3 + 4i
Comparing real and imaginary parts,
a 2 + b2 + 2a = 3 and 2b = 4 ⇒ b = 2
Then a 2 + 22 + 2a = 3
a 2 + 2a + 1 = 0
( a + 1)2 = 0
a = −1
∴ w = −1 + 2i

2
dI
4 4 = 2 − 3I
dt
4
∫ 2 − 3I dI = ∫ 1 dt

4
− ln 2 − 3I = t + c
3
3
ln 2 − 3I = − t + c '
4
3
− t +c'
2 − 3I = ± e 4

3
− t
= Ae 4
3
− t
3I = 2 − Ae 4

When I = 2, t = 0 ,
6 = 2− A
A = −4
3
− t
∴ 3I = 2 + 4e 4
2 − t
3
I = 1 + 2e 4 
3  

3
− t
When t → ∞, 2e 4 →0
2
∴ I→
3

2x + 7
5 y=
x+2
2( x + 2) + 3
=
x+2
3
= 2+
x+2
where A = 2 and B = 3 (shown)

3
1 3
To transform y = into y = 2 + .
x x+2
1
1) Translate the graph of y = in the negative x-direction by 2 units.
x
1
2) Stretch the graph of y = parallel to the y-axis by a factor 3.
x+2
3
3) Translate the graph of y = in the positive y-direction by 2 units.
x+2

2x + 7
y=
x+2
7 7
When x = 0, y = and y = 0, x = −
2 2
y

2x + 7
y=
x+2

(0, 72 )

y=2

( − 72 , 0) O x

x = −2

  1    2 
6 OA = −1 and OB =  4 
 
2 1
   
 
(i) OA ⋅ OB
 1   2
=  −1  ⋅  4 
 2  1
   
= 2 − 4
+2 
= 0
Since OA ⋅ OB = 0 , OA is perpendicular to OB . (shown)

4
A 1 M 2 B
(ii) Given AM : MB = 1 : 2, we have | | |
By Ratio Theorem,
 
 2OA + OB
OM =
3
 1 2 
1       1   4 2 5
4
= 2 −1 + 4 = 2 = i + j + k
3   2   1  3  5  3 3 3
      

1   C
(iii) Area of ∆OAC = OA × OC
2
1   
1 −4
=  −1  ×  2 
22  2
    O A
1
−6 
=  −10 
2  −2 
 
1 2
= 6 + 102 + 2 2
2
1
= 140 = 35
2

7 P( z ) = 0 has real coefficients.


(i) Since reiθ is a root, re−iθ is also a root.
A quadratic factor of P( z ) is z − reiθ ( )( z − re ) − iθ

= z2 − ( r e + re ) z + r
iθ − iθ 2

= z 2 − r ( cos θ + i sin θ + cos ( −θ ) + i sin ( −θ ) ) z + r 2


= z 2 − r ( cos θ + i sin θ + cos θ − i sin θ ) z + r 2
= z 2 − 2rz cos θ + r 2 (shown)
6
(ii) z = −64
= 64(−1)
= 64e(π + 2 kπ )i
1
z = 64e(π + 2 kπ )i  6
(2 k +1)π i
= 2e 6 where k = −3, −2, −1, 0,1, 2
−5π −3π −π π 3π 5π
i i i i i i
= 2e 6 , 2e 6 , 2e 6 , 2e 6 , 2e 6 , 2e 6

5
(iii) z 6 + 64
(
= z − re 6 i
π

)( z − re )( z − re )( z − re )( z − re )( z − re )
− π6 i 3π
6 i − 36π i 5π
6 i − 56π i

 π    3π  2  2  5π  2
=  z 2 − 2(2) z cos   + 2 2  z 2 − 2(2) z cos   + 2  z − 2(2) z cos  +2 
 6   6    6  
( )( )(
= z 2 − 2 3z + 4 z 2 + 4 z 2 + 2 3z + 4 )

  1    −2 
8 Given OA = 2 , OB =  3 
  and plane p : 3 x − y + 2 z = 17
 4 1
   

  −2   1   −3 
(i) AB =  3  −  2  =  1 
 1   4   −3 
     
1 3
Equation of line l is r = 2 + λ −1
   , λ ∈
 4 3
   
3
Equation of plane p is r ⋅  −1 = 17
2
 

To find intersection between l and p,

 1   3   3 
 2  + λ  −1  ⋅  −1 = 17
 4     
   3   2 
( 3 − 2 + 8 ) + λ ( 9 + 1 + 6 ) = 17
9 + 16λ = 17
16λ = 8
1
λ=
2
 1  1  3   2.5 
∴ Position vector of the point of intersection is r =  2  +  −1 =  1.5 
 4  2  3   5.5 
     
i.e. coordinates of the point of intersection are ( 2.5 , 1.5 , 5.5) .

6
(ii) Let θ be the angle between l and p.

3 3
 −1 ⋅  −1
3 2
sin θ =    
9 +1+ 9 9 +1+ 4
9 +1+ 6
=
19 14
16
=
19 14
θ = 78.8 ( to nearest 0.1 )

(iii) Let C be the point of intersection between l and p and F be the foot of the
perpendicular from point A to plane p .
Then perpendicular distance form A to plane p is AF.
AF
Now sin θ =
AC

  2.5   1   1.5 


AC =  1.5  −  2  =  −0.5 
 5.5   4   1.5 
     
AC = 1.52 + 0.52 + 1.52 = 4.75

∴ AF = AC sin θ
= 4.75 sin 78.820
= 2.14 (3 s.f)

  3 
AC ⋅  −1
2
 
OR AF = = ... = 2.14 (3.s.f)
9 +1+ 4

7
9 y = e x − 3x
(i) Using the GC, α = 0.619 and β = 1.512 (correct to 3 decimal places)

(ii) Assuming that the sequence converges to some constant l ,


then xn → l and xn +1 → l as n → ∞
Given xn +1 = 13 e xn , we have
l = 13 el
3l = el
el − 3l = 0
Since α and β are the roots of the equation e x − 3 x = 0 , l = α or l = β .
Hence the sequence converges to either α or β .

(iii) For x1 = 0 , the sequence converges to α.


For x1 = 1 , the sequence converges to α.
For x1 = 2 , the sequence diverges.

1 1
(iv)
3
( 3
)
Since xn +1 = 13 e xn , xn +1 − xn = e xn − xn = e xn − 3 xn .
xn
If α < xn < β , e − 3 xn < 0 as observed from the graph.
∴ xn +1 − xn < 0, i.e. xn +1 < xn .
If xn < α or xn > β , e xn − 3 xn > 0 as observed from the graph.
∴ xn +1 − xn > 0, i.e. xn +1 > xn .

(v) When x1 = 0 , we have x1 < α so xn +1 > xn from (iv). The sequence x1 , x2 , x3 , …,


is an increasing sequence which converges to α (from below).

When x1 =1, we have α < x1 < β , so xn +1 < xn from (iv). The sequence x1 , x2 ,
x3 , …, is a decreasing sequence which converges to α (from above).

When x1 = 2 , we have x1 > β , so xn +1 > xn from (iv). The sequence x1 , x2 , x3 , …,


is an increasing sequence which diverges.

8
Screen shots for 9(iii)

10 GP : common ratio r
AP : 1st term a, common difference d where a, d ≠ 0
Given 1st term of GP = 1st term of AP = a
(i) Also, ar = a + 3d -------- (1)
ar 2 = a + 5d -------- (2)
1
From (1), d = (ar − a ) -------- (3)
3
Substitute (3) into (2),
1
ar 2 = a + 5 ⋅ (ar − a )
3
2
3ar = 3a + 5ar − 5a
3ar 2 − 5ar + 2a = 0
Since a ≠ 0 , 3r 2 − 5r + 2 = 0 (shown)

(ii) 3r 2 − 5r + 2 = 0
(3r − 2)(r − 1) = 0
2
r= or r = 1
3
Since d ≠ 0 , r ≠ 1 from (3)
2
∴r =
3
Since r < 1 , the geometric series is convergent.
a a
∴ S∞ = = = 3a
1 − r 1 − 23

9
n
(iii) Sum of 1st n terms of AP = S = [2a + (n − 1)d ]
2
Now S > 4a , where a > 0
n
i.e [2a + (n − 1)d ] > 4a
2
2 1 2  1
Substitute r = into (3), d =  a − a  = − a
3 3 3  9
n  1 
∴  2a + (n − 1)  − a   > 4a
2  9 
 1 
na  2 − (n − 1)  > 8a
 9 
18n − n(n − 1) > 72 since a > 0
n 2 − 19n + 72 < 0
Using G.C, 5.23 < n < 13.77 .
Since n ∈  + , the set of possible values of n is {6, 7,8,9,10,11,12,13} .

π
11 x = cos 2 t , y = sin 3 t , 0≤t ≤
2
(i)
y

When t = 0 , x = 1 , y = 0
1
π
When t = , x = 0 , y =1
2

O 1 x

(ii) x = cos 2 t y = sin 3 t


dx dy
= 2 cos t (− sin t ) = 3sin 2 t (cos t )
dt dt

dy 3sin 2 t cos t 3
∴ = = − sin t
dx −2 cos t sin t 2
dy 3
i.e. = − sin θ
dx t =θ 2

10
Equation of tangent at the point (cos 2 θ , sin 3 θ ) is
y − sin 3 θ 3
2
= − sin θ
x − cos θ 2
3
y − sin 3 θ = − sin θ ( x − cos 2 θ )
2
At Q, y = 0 ,
3
− sin 3 θ = − sin θ ( x − cos 2 θ )
2
2 sin θ = 3sin θ ( x − cos 2 θ )
3

sin θ (3 x − 3cos 2 θ − 2sin 2 θ ) = 0


1
sin θ = 0 or x =
3
( 3cos2 θ + 2sin 2 θ )
At R, x = 0 ,
3
y − sin 3 θ = sin θ (cos 2 θ )
2
3
y = sin θ (cos 2 θ ) + sin 3 θ
2
1
= sin θ (3cos 2 θ + 2sin 2 θ )
2
1 1 1
∴ Area of ∆OQR = ⋅ ( 3cos 2 θ + 2sin 2 θ ) ⋅ sin θ (3cos 2 θ + 2sin 2 θ )
2 3 2
1 2
= sin θ ( 3cos 2 θ + 2sin 2 θ ) (shown)
12

1 dx π
(iii) Required area = ∫ y dx where = 2 cos t (− sin t ) When x = 0 , t =
0 dt 2
0
= ∫π sin 3t ( − 2sin t cos t ) dt When x = 1 , t = 0
2

0
= −2 ∫π cos t sin 4t dt
2
π

= 2 ∫ cos t sin 4t dt (shown)


2

11
du
Let u = sin t , = cos t
dt
When t = 0 , u = sin 0 = 0
π π
When t = , u = sin =1
2 2
π

∴ Required area = 2 ∫ cos t sin 4t dt


2

0
1
= 2 ∫ u 4 du
0
1
 u5 
= 2 
 5 0
2
=
5

Note : Do use the GC to CHECK your answer.


π
fnInt(2cos(X)(sin(X))^4, X, 0, ) = 0.4
2

Screen shots for Q11(i)

12